Identification and Evaluation of Waste in Animal Feed Production Line Using an Integrated VSM and VALSAT Approach - Putri Anggita; Piguna Wati; Sabiq Dimas Izzuddin; M. Nushron Ali Mukhtar (Institut Teknologi Dirgantara Adisutjipto, 2026)
This study evaluates the application of Lean Manufacturing principles using the Value Stream Mapping (VSM) methodology to systematically identify and eliminate waste in the production operations of the breeding animal feed division of PT XYZ. This issue is crucial because the high demand for feed products, especially in the breeder division of PT XYZ, requires the company to make continuous process improvements. This study aims to evaluate the application of Lean Manufacturing principles using the Value Stream Mapping (VSM) and Value Stream Analysis Tools (VALSAT) approaches to identify and eliminate waste in the livestock feed production line. Primary data collection included direct observation studies, structured questionnaires, and in-depth interviews with operators, supplemented by secondary data obtained through a systematic literature review. The application of Value Stream Analysis Tools (VALSAT) revealed that process inefficiencies mostly stemmed from waiting time, product defects, and excessive production output. The VSM analysis of the current condition showed a value-added ratio of 69.05%, with the mapping of the future condition after intervention showing an increase to 70.49%. [Deleted]. This study produced actionable operational recommendations, enabling PT XYZ to align its production system with contemporary industry benchmarks for optimal performance.